Análisis sociométrico de la Revista de Psicología de la Pontificia Universidad Católica del Perú (1983-1992) - Vargas López, Marco (1996)
Peruvian psychology is estudied through one of its most representative periodical publications: The Psychological Journal -published by Peruvian Pontifical Catholic University-,covering from 1983 ro 1992 (Vols. 1-10). Using a bibliometric methodology, in asociometric slope, the journal is analyzed according ro its collaborators (authors of anidesand reviews), identifying institutions they represent, their professional arcas, nationality,genre distribution, number of anides signed, formulation of groups of collaboration andproductivity.